Impact of Concrete-Pictorial-Abstract Approach with Collaborative Lesson Research on Year Four Pupils' Proficiency in Perimeter. - Shafiee, Mohd Shafian; Chew Cheng Meng (Pertanika Journal of Social Sciences & Humanities, 2021)
The purpose of this study was to determine whether the concrete-pictorial-abstract (CPA) approach developed based on the Collaborative Lesson Research (CLR) cycles can positively impact Year Four pupils' proficiency in perimeter. Counterbalanced design was used with pre- and post-test in every CLR cycle. The participants involved were three groups of pupils totaling 115 pupils and a group of three teachers. The sampling used was cluster random sampling. A paired-samples t test was used to determine whether there is a significant difference between the pre- and post-test for each CLR cycle while a one-way ANOVA test was used to analyze if there is an increase in proficiency from the first, second and third CLR cycles. The results indicated that there was an increase in the mean post-test scores compared to the mean of pre-test scores and the mean difference between the first, second and third CLR cycles. In conclusion, the CLR cycle carried out helped teachers in developing better teaching plans based on the CPA approach as well as enhancing pupils' proficiency in the perimeter.